To a beautiful soul. Inscriptions on lead mirrors (Collection of Roman Antiquities, Hungarian National Museum) - Németh , György; Szabó, Ádám (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
There is a collection of several hundred small Roman lead mirrors (former private collection) in the Hungarian National Museum. Greek or Latin inscriptions can be read on 17 mirrors. The present study publishes these items along with the drawings of the inscriptions. Such mirrors were found mainly in graves of women, functioning as escorts to the souls of the dead and as apotropaic amulets.